Knowledge, attitude and practice on infant and young child feeding practices (IYCF) in Raksirang, Makwanpur, Nepal - Kandel, Kamal Prasad; Kafle, Sindhu (Journal of Chitwan Medical College, 2018)
Nepal is one of the developing Countries in the South Asia. Early childhood is very important and the crucial period for the proper physical, mental and emotional development. Therefore child should be looked especially at this period. In Nepal, child below two years are suffering from malnutrition the most. The initiation of breastfeeding within one hour of birth has numerous nutritional and immunological benefits and has been found to reduce neonatal mortality. An improper feeding practice among young children particularly 6-23 months is a major cause of malnutrition. Thus, the present study has been focused on feeding practices of fewer than two years children. The study was quantitative study. Main objective of the study was to know the feeding practices of under two years children after implementation of Baal Vita(Sprinkles) program in Raksirang VDC of Makwanpur district. Questionnaire was related to the Baal Vita(Sprinkles) program, Breastfeeding practices and Complimentary feeding practices. Altogether 132 mothers were taken for the study. The structured questionnaire was developed, pretested and used to collect the information. After the collection of data, it was analyzed by using SPSS 17.0.Also the data was presented in different tables to make it more clear and specific. Among 132 of the respondent, majority of the respondent were aged between21-25 years. 37.88% mothers were illiterate and only 1.52% had secondary level education. Some of the respondents were pregnant before the age 20 years. One of the mother was give birth to her child at age of 15 years.68.18% respondent had first Breastfed their child with in 1 hour of birth. Colostrum feeding was seen not good. This study found Still practice of squeezing colostrum. Current breastfeeding practice is seen good. About 88.64% of the respondent had started giving complementary food in correct time.